Law Enforcement in The Eradication of Narcotics Crimes Against Drug Addicts and Abusers - Achmad Yuliandi Erria Putra; Mirawaty Nurhamidin; Dede Cairul (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Law enforcement for narcotics addicts and abusers mostly applies prison sentences as in the Indonesian criminal justice system. It makes the prison to overcrowding. On the other hand, other law enforcement alternatives are deemed proven to be able to eradicate narcotics addicts and abusers and provide great benefits for all parties without applying penalties in the form of criminal sanctions. It is the application of a restorative justice approach in law enforcement for narcotics addicts and abusers. This research is focused on discussing the background of the problem: how to implement restorative justice in law enforcement for addicts and drug abusers. This study uses empirical normative research methods. The study's findings led law enforcement to adopt a restorative justice approach when dealing with narcotics addicts and abusers. It is accomplished by offering treatment in the form of medical or social rehabilitation. The spirit of restorative justice is essentially embodied in Article 54 of Narcotics Law Number 35 of 2009, which orders addicts and abusers to be treated medically or socially. However, it has not been implemented optimally and comprehensively. There is still a discrepancy in how law enforcement handles narcotics addicts and abusers. Restorative justice, including the provision of medical or social rehabilitation, should be implemented at all stages of law enforcement: investigation, prosecution, and even court appearances. However, until today, medical or social rehabilitation has only been provided by a judge's order following a court trial.Keywords: law enforcement; narcotics crime; restorative justice